Karl Löwith: a prosperous mind in a destitute time - Fox, Kevin W. (2012)
Karl Löwith is heralded by Richard Wolin in his work, Heidegger's Children, as being “one of the most significant figures of twentieth century German philosophy” and was praised by Hans-Georg Gadamer as being the best German writer of his time. Löwith’s philosophy has, however, not received due attention since his death in 1973. The current project attempts to show Löwith’s continued importance for modern philosophy by pulling his various critiques together and showing their proper role in his work as a whole.
Online publiziert: 2015
Keywords: Hochschulschrift; Löwith, Karl; Rezeption; Heidegger, Martin; Universität Heidelberg / Philosophisches Seminar